Employee unrest at Nokia India - Varkkey, Biju, (SAGE Business Cases., 2017)
The case focuses on the closure of the Nokia manufacturing plant in India due to steep reduction in orders from Microsoft and accusations from the Indian Tax department of tax evasion. In mid-April 2014, the Nokia offered Voluntary Retirement Scheme (VRS) to its employees. Within a months' time, 2,000 employees opted for VRS, fearing that they would not get anything once the management closed the offer. The unions approached the management, state government and central government for an intervention to stop the closure of the Chennai plant, which would leave 30,000 direct and indirect employees jobless. However, these talks failed, and the plant finally shut its operations on November 1, 2014. The case invites students to consider alternative course of action that Nokia's management could have taken for the benefit of its employees.